Penerapan Metode Failure Mode And Effect Analysis (FMEA) Pada Industri Pelayaran Dalam Mengidentifikasi Potensi Kegagalan Komponen Mesin Induk ( Studi Kasus di Kapal Xyz ) - Daryanto, Daryanto (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
The main engine of a ship plays a crucial role in supporting its operations. Failure in this engine can have fatal consequences, both in terms of safety and economic impact. This study applies the Failure Mode and Effect Analysis (FMEA) method to the main engine of Ship XYZ to identify potential failure modes and calculate risk levels based on the Risk Priority Number (RPN). Operational data, interviews with the chief engineer, machinists, technicians, and historical failure analyses were used to assess the parameters of Severity (S), Occurrence (O), and Detection (D). The results indicate that fuel pipe leakage has the highest RPN value (405), followed by rotor damage in the turbocharger (245), and mechanical failure in the valve (224). Recommended improvements include enhancing maintenance of the fuel pipe system and conducting regular visual inspections, routine cleaning and lubrication, vibration inspections for turbocharger components, as well as using high-quality lubricants and cleaning carbon residue buildup on intake valves. Keywords: FMEA, Main Engine, Potential Failure, Ship, RPN.